THE INFLUENCE OF ONLINE LEARNING ON STUDENT MOTIVATION BEHAVIOR AT SMA NEGERI 1 LAWA - Nella BR Purba (Prodi Bimbingan Konseling Universitas Negeri Manado, 2022)
This study aims to determine the effect of online learning on student learning motivation at SMA Negeri 1 Lawa in the 2020/2021 school year. This research was conducted using a quantitative method, by taking a sample of 65 students of SMA Negeri 1 Lawa in the academic year 2020/2021. Data were collected through a questionnaire with a Likert scale. The data analysis technique used simple linear regression analysis with the help of a computer program SPSS 23 for windows. The results showed that there was an effect of online learning on students' motivational behavior. The regression equation Y = 57.480 - 0.401 X with the quantitative increment of the two variables was 1: 0.401 this comparison shows that if there is an increase of one time / unit in the online learning variable (X) then there will be an increase of 0.401 in the student learning motivation variable (Y). The regression equation is significant or will not be tested using the Fcount value at the significant level of 0.05. Meaning that Ha was accepted and Ho was rejected. The conclusion is that the hypothesis which says there is an effect of online learning on student learning motivation at SMA Negeri 1 Lawa is accepted and significant, this is indicated by the value of the regression coefficient (F) of 20.025 with a significant 0.000.